'Farewell Red Balloon' – visual analysis of illustrations inspired by a children's book. Issue 3 (3rd July 2018) - Kohn, Ayelet; Weissbrod, Rachel
Abstract : This paper deals with illustrations created as sequels to a children's book. The visual analysis is conducted in the framework of translation and adaptation studies and attempts to find a place for sequels in this framework. It has been claimed that sequels cannot be grouped together with translations and adaptations because there is a difference between never wanting a story to end and wanting to retell the same story. However, sequels share with adaptations and translations major features, mainly the balance between repetition and change and the possibility of reinterpreting the source text. With this in mind, we investigate a 2014 exhibition of illustrations titled 'Farewell Red Balloon'. Each of them adds a successive scene to the Hebrew children's classic A Tale of Five Balloons . The wide range of sequels in continuation of one source text provides an opportunity to deal with questions such as: How do the sequels relate to the source text? What additional intertextual relations do they establish? Do the setting, genre and target audience remain the same, or change? Similar questions are raised when dealing with translations and adaptations. In the present context, they apply to sequels which employ one mode, the visual.